Pediatric bilateral large concurrent thalamic glioblastoma: An unusual case report - Pandey, Nityanand (Medknow Publications & Media Pvt Ltd, 2014)
Bilateral thalamic tumors are rare. Pediatric bilateral thalamic glioblastomas are even rarer, only five cases reported in the English literature till date. The clinical presentation, natural history, and prognosis of pediatric thalamic tumors are still relatively obscure. In this article, we report an 8-year-old patient with large bilateral thalamic glioblastomas and briefly discuss its clinical presentation, possible modalities of management, and prognosis, in the light of available literature.